Practical approach to aesthetics going beyond art appreciation - Aquino, Eliza Driz; Santillana, Priscilla Mizpah P. (Books Atbp. Publishing Corp., 2015)
"The book, A Practical Approach to Aesthetics: Going Beyond Art Appreciation, is a simplified discussion of the nature of art, beauty, and taste. It also deals with the creation and appreciation of beauty. Furthermore, it elaborates the different theories and concepts of art that will help students in their judgment of what is beautiful and important."--Preface